Argumentasi Nasabah Non-Muslim Menjadi Nasabah di Bank Syariah Mandiri Kantor Cabang Lumajang - Nurhafid Ishari; Aditya Aditya Rizki (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2017)
The rapid development of sharia banking is not only supported by government regulation but also supported by the quality and service of sharia banking which is getting better. The service, quality, variety of products, minimization of risk that gives profit to customers and the professionalism of sharia banking managers that are increasingly improving now make sharia banking can slowly compete with conventional banking professionally. Sharia banking that proved to be more just and profitable is now growing and gain the trust of the wider community, in this case not only Muslim community but also non-Muslim community. This research uses quantitative method, with field research approach and is descriptive. Technique of collecting data using questioner with sampling technique used is convenience sampling technique. The data analysis uses descriptive statistics, by determining the mean using the mode. The result of this research is the argumentation of non-Muslim customers to customers in syariah banking especially in Bank Syariah Mandiri Lumajang Branch Office there are six factors that are cultural factor, social class factor, learning experience factor, personality factor, self concept factor, attitude and belief factor. The most prompting factor for non-Muslim customers to choose Bank Syariah Mandiri Lumajang Branch Office is a cultural factor in the sixth indicator of service related to Bank Syariah Mandiri.